2019
DOI: 10.3389/fneur.2019.01066
|View full text |Cite
|
Sign up to set email alerts
|

rs3764435 Associated With Parkinson's Disease in Mexican Mestizos: Case-Control Study Reveals Protective Effects Against Disease Development and Cognitive Impairment

Abstract: Parkinson's disease (PD) is the second most common movement disorder. Genetic risk factors provide information about the pathophysiology of PD that could potentially be used as biomarkers. The ALDH1A1 gene encodes for the aldehyde dehydrogenase enzyme, which is involved in the disposal of toxic metabolites of dopamine. Due to the cytotoxic nature of aldehydes, their detoxification is essential for cellular homeostasis. It has been reported that ALDH1A1 expression levels and activity are decreased in PD patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
(35 reference statements)
2
5
0
Order By: Relevance
“…The proposed mechanism acquires relevance if one considers its specificity for dopaminergic nigrostriatal neurons, at the early stages of PD neurodegeneration. The translational relevance of our results also hinge on epidemiological studies that correlated an increased risk of developing PD with the exposure to drugs, pesticides, and chemicals that act as ALDHs inhibitors 20,40 , enhanced by some genetic variations on Aldh1a1 and Aldh2 genes that were recently identified 20,55,56 . Unfortunately, only a few studies investigated the presence of DOPAL-modified αSyn species in PD autoptic samples, mostly because of the lack of reliable tools for their detection.…”
Section: Discussionsupporting
confidence: 53%
“…The proposed mechanism acquires relevance if one considers its specificity for dopaminergic nigrostriatal neurons, at the early stages of PD neurodegeneration. The translational relevance of our results also hinge on epidemiological studies that correlated an increased risk of developing PD with the exposure to drugs, pesticides, and chemicals that act as ALDHs inhibitors 20,40 , enhanced by some genetic variations on Aldh1a1 and Aldh2 genes that were recently identified 20,55,56 . Unfortunately, only a few studies investigated the presence of DOPAL-modified αSyn species in PD autoptic samples, mostly because of the lack of reliable tools for their detection.…”
Section: Discussionsupporting
confidence: 53%
“…For rs3764435, there was an ALDH1A1 yin yang haplotype block (haplotypes that have opposite allelic configuration) association with alcohol dependence in Finns driven by this SNP. 44 In addition, Salas-Lea et al 45 found an association between Parkinson's disease and rs3764435 in a Mexican mestizo population. With regard to rs63319, the dominant minor allele of it advances the onset age of alcoholism in non-Hispanic Caucasian males.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, mRNA levels of ALDH1A1 in peripheral blood are significantly decreased in PD patients compare to control cases (50). Moreover, clinical studies showed that the genetic variability of ALDH1A1 is a good predictive factor for PD diagnosis and the progress rate of the disease (51)(52)(53). Yet, if vitamin A is necessary for ALDH1A1 expression, a decreased vitamin A bioavailability may constitute a risk factor for the disease.…”
Section: Discussionmentioning
confidence: 99%